A COMPATIBLE ESTIMATION MODEL OF STEM VOLUME AND TAPER FOR Acacia mangium Willd. PLANTATIONS - Krisnawati, Haruni (Indonesian Journal of Forestry Research, 2016)
This study describes the establishment of a compatible volume estimation model for Acacia mangium Willd on the basis of 279 felled sample trees collected from the A. mangium plantation stands in South Sumatra, Indonesia. The model comprises of a total volume model and a stem taper model, which is compatible in the sense of the total volume obtained by integration of the taper model being equal to that computed by the total volume model. Several well-known total volume functions were evaluated including constant form factor, combined variable, generalized combine variable, logarithmic, generalized logarithmic and Honer transformed variables. A logarithmic model was determined to be the best and was then used as the basis for deriving the taper model. Appropriate statistical procedures were used in model fitting to account for the problems of heteroscedasticity and autocorrelation that are associated with the construction of volume and taper functions. The simultaneous fitting method of the Seemingly Unrelated Regression (SUR) improved the parameter estimates and goodness-of-fit statistics while ensuring numeric consistency among the component models and reducing the total squared error obtained by an independent fitting method. The developed model can be used to estimate total stem volume, merchantable volume to any merchantability diameter limit at any height, and (possibly) height of any diameter based on only easily measurable parameters such as diameter at breast height and total tree height for the species analysed.